IMPLEMENTASI STRATEGI RELATING, EXPERIENCING, APPLYING, COOPERATING, TRANSFERRING (REACT) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA MATERI LAJU REAKSI DI SMA NEGERI 11 PEKANBARU - Rukaiyah Rukaiyah; Erviyenni Erviyenni; Asmadi M Noer (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Research on the implementation of REACT strategy aims for improve learning achievement on reaction rate material and knowing kategori of learning achievement improvement of learners in class X I SMA Negeri 11 Pekanbaru After given the tests of normality and homogeneity The sample of research consisted two class, obtained the students of class XI IPA2 as the experimental class and the students of class XI IPA4 as the control class. They were randomly determined. The Experimental class is a class which was given a treatment by applying REACT strategy, includes five steps Relating, Experiencing, Applying, Cooperating, and Transferring. This research used experiment with design Randomized Control Group Pretest-Posttest. The data were analyzed by using t-test. Based on the result of data analysis, it obtained tscore > ttable (5,68 > 1,67), meaning the implementation of the REACT strategy can improve student learning achievement there is material rate reaction in class X I MIA SMA Negeri 11 Pekanbaru. The improvement category in learning achievement on the material rate reactions in the experimental class include high category with normalized N- gain of 0.71 .Keywords: Strategy REACT , Learning Achievement, Rate Reaction